1994
DOI: 10.1007/bf00193789
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of K+-channels in p-neurones of the leech CNS by phosphorylation

Abstract: Two types of potassium channels of identified (p-) neurones of the leech (Hirudo medicinalis) were investigated by using the patch-clamp technique. The open-state probability of these channels in cell-attached patches can be reduced by addition of 5-hydroxytryptamine to the bath solution. After excising the patches the application of alkaline phosphatase to the cytosolic face of the patch increases the open probability. The 5-HT1A-receptor agonist buspirone mimics the effect of 5-HT. Our experiments show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…An extensive characterization of Na + , K + , and Ca 2+ currents in the leech CNS has previously been examined using voltage-clamp measurements, ion replacement, and pharmacological blockers to understand the role that these ionic currents play in cultured leech Retzius (R), anterior pagoda (AP) and sensory neurons, attributing different membrane properties to distinct ion channel complements [ 49 ]. In the pressure-sensitive mechanosensory (P) neurons, it was shown that the probabilities of K + -channel open and closed states could be modulated by different phosphorylation events mediated by a 5HTR subtype [ 50 ]. The fast-transient A-type potassium current also increased with the age of cultured AP neurons, while other potassium currents remained unchanged [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive characterization of Na + , K + , and Ca 2+ currents in the leech CNS has previously been examined using voltage-clamp measurements, ion replacement, and pharmacological blockers to understand the role that these ionic currents play in cultured leech Retzius (R), anterior pagoda (AP) and sensory neurons, attributing different membrane properties to distinct ion channel complements [ 49 ]. In the pressure-sensitive mechanosensory (P) neurons, it was shown that the probabilities of K + -channel open and closed states could be modulated by different phosphorylation events mediated by a 5HTR subtype [ 50 ]. The fast-transient A-type potassium current also increased with the age of cultured AP neurons, while other potassium currents remained unchanged [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…5HT modulates several membrane conductances in leech neurons. For example it modulates Cl Ϫ channels (Ali et al 1998;Lessmann and Dietzel 1995) and K ϩ channels (Goldermann et al 1994) in P sensory neurons. In addition, 5HT modulates voltage-activated K ϩ channels (Acosta-Urquidi et al 1989) and a Cl Ϫ conductance (Munsch and Schlue 1993) in the Retzius cells.…”
Section: Role Of the Na ϩ /K ϩ Atpase In The Ahp Amplitude Enhancementmentioning
confidence: 99%
“…These E m changes are mainly due to the direct activation of 5-HT-gated Cl Ϫ channels (Lessmann and Dietzel, 1995b;Ali et al, 1998) as well as to the activation of unselective cation channels via metabotropic 5-HT receptors (Catarsi and Drapeau, 1997;Drapeau et al, 1989). Beside these well-characterized systems, the existence of other 5-HT-dependent conductances has been proposed (Goldermann et al, 1994;Lessmann and Dietzel, 1991;Walz and Schlue, 1982).…”
Section: Introductionmentioning
confidence: 96%